ANALISIS HASIL PENGUJIAN SONDIR UNTUK MENGETAHUI PENINGKATAN KEKUATAN TANAH SANGAT LUNAK DI LOKASI GATE HOUSE DALAM PEKERJAAN “GROUTING AT SEMARANG PUMPING STATION & RETARDING POND” - Hendry Tri Wibowo (Geological Engineering E-Journal, 2013)
The water building structure at the mouth of the Semarang river as a flood prevention building in Panggung Lor village is a high settlement risk building structure. This is caused by lithological estuary region consisting predominantly of fine clay-sized sediments with a low level of consistency. The low value of consistency is comparable to the soil bearing capacity value of the water structure foundation pillars. Analysis of the Semarang river Gate House cone penetration test results aims to determine the increase of soil bearing capacity with the method of grouting on the site by using the cone penetration test results. From the three trial soil penetration test location before the grouting process, the very soft clay was found in the 0,6 to 15 metres in depth with 1 up to 4 kg/cm2 of cones resistance value. For deepness 14,00 m - 20,00 m there are soft clay with cones resistance value ( qc) 5 - 8 kg / cm2.. The determining processes of soil bearing capacity then consist of several processes. Based on this, the ultimate bearing capacity mean value before the grout process is about 19,45 with the allowable bearing capacity mean value about 3,97 ton.   The ultimate bearing capacity mean value after the grout is about 38,557 ton with the allowable bearing capacity mean value 7,8625 ton. It appears that the increase of ultimate bearing capacity is about 98 % or about 1,9 times greater than before.